PP.19.21: BIATRIAL ATRIAL PHASIC FUNCTION AND MECHANICS IN SUBJECTS WITH METABOLIC SYNDROME. (June 2015) - Tadic, M.; Celic, V.; Ivanovic, B.
Abstract : Objective: We compared phasic function and mechanics of the left atrium (LA) and right atrium (RA) between the subjects with metabolic syndrome (MS) and healthy controls. Design and method: This cross-sectional study involved 58 subjects with metabolic syndrome and 55 healthy controls matched by sex and age. Metabolic syndrome was defined by the presence of at least three ATP-AHA-NHLB criteria. Laboratory analyses and comprehensive echocardiographic examination including two-dimensional strain analysis were done to all participants. Results: LA and RA reservoir function, evaluated by total emptying fraction, was decreased in the MS subjects comparing with control group (LA: 65 ± 7 vs. 60 ± 6 % p < 0.01; RA: 63 ± 6 vs. 57 ± 5 % p < 0.01). Biatrial conduit function, assessed by passive emptying fraction, was also reduced in the individuals with MS (LA: 47 ± 4 vs. 41 ± 3 %, p < 0.01; RA: 44 ± 4 vs. 40 ± 4 %, p < 0.01). Active function of both atria was increased in the MS group comparing with controls (LA: 40 ± 5 vs. 44 ± 5 %, p < 0.01; RA: 38 ± 4 vs. 43 ± 5 %, p < 0.01). Two-dimensional strain analysis of the atrial phasic function revealed that biatrial total and passive functions were deteriorated, whereas biatrial active function was increased in the MS group. In the whole study population LA longitudinal strain correlated with blood pressure (r = -0.43, p < 0.01), fasting glucose (r = -0.38, p < 0.01) and waist circumference (r = -0.34, p < 0.01). However, among MS criteria, only blood pressure level (β=-0.39, p < 0.01) and waist circumference (β=-0.3, p < 0.01) were independently associated with LA longitudinal strain. Additionally, RA longitudinal strain correlated with blood pressure level (r = -0.37, p < 0.01) and waist circumference (r = -0.25, p = 0.02), among the MS parameters. Only blood pressure level was independently associated with RA longitudinal strain (β=-0.29, p = 0.01). Conclusions: Biatrial phasic function is significantly impaired in the MS subjects. Blood pressure, fasting glucose and abdominal obesity are the most responsible MS criteria for deterioration of LA and RA mechanics.